Heterogeneous oceanic mass distribution in GRACE observations and its leakage effect. Issue 1 (10th January 2020) - Yi, Shuang; Heki, Kosuke
SUMMARY: Signal leakage between the land and ocean is a challenge in using Gravity Recovery and Climate Experiment (GRACE) observation data to study global mass redistributions. Although the leakage occurs in both directions, more attention has been paid to the land-to-ocean leakage and less to the ocean-to-land leakage. Here, we show that the ocean-to-land leakage is non-uniform and non-negligible and propose a new forward modelling method to fully consider bi-directional leakages with the help of the global Ocean ReAnalysis System ORAS5. This observation-driven model could significantly reduce the variations in ocean grids and thus decrease the ocean-to-land leakage. The results with different treatment of the ocean signal leakage are compared. We find that failing to consider the ocean-to-land leakage will cause an underestimation of ∼20 per cent in the seasonal variation and will introduce a bias of several giga-tons in the secular trend. Although the uniform and non-uniform model have similar results in the global average of seasonal mass variations, the non-uniform ocean model is necessary in most places, especially near the Arctic Ocean, the Sea of Japan and the Gulf of Carpentaria. Despite these achievements, we also point out that there is still much room for improvement in ocean mass models, particularly in long-term trends. Our results indicate the importance of the ocean-to-land leakage correction in the mass estimation in coastal land areas using the GRACE data.